Can porous tantalum acetabular cups and augments restore the hip centre of rotation in revision hip arthroplasty? Long-term results. - Concina, Chiara; Crucil, Marina; Gherlinzoni, Franco (Acta Biomedica Atenei Parmensis, 2022)
Background and aim: Loss of bone stock is the main problem in revision hip arthroplasty. Porous tantalum cups and augment constructs are possible solutions. The aim of this study was to describe results at an average follow-up of 10 years using these cups. Methods: 25 patients underwent to revision hip arthroplasty with porous tantalum cups. Acetabular bone defects were classified according to Paprosky’s in type II and III. All patients were reviewed clinically and radiographically at an average follow-up of 10 years (range 8.5 to 13 years). Changes in inclination angle of the cup and position of the hip centre of rotation (COR - measured and calculated using Pierchon’s method), and possible periacetabular radiolucency lines were assessed. Results: A statistically significant improvement in Harris Hip Score and hip range of motion was observed. The hip COR had been lowered by 19.33 mm after revision and no changes in COR position had been measured at follow-up. Kaplan-Meier survivorship was 100% at an average follow-up of 10 years, considering acetabular revision for any reasons as primary endpoint. 88% of patients was satisfied. Complications were 3 dislocations, 4 asymptomatic heterotopic ossifications and 1 partial reabsorption of greater trochanter. Conclusions: Porous tantalum cups and augments can be considered a valid solution in acetabular revisions for addressing massive bone defects and restoring the hip COR.